Antibacterial activities of a new stabilized thienamycin, N-formimidoyl thienamycin, in comparison with other antibiotics. - Kesado, T (1980)
The in vitro activity of a new crystalline derivative of thienamycin, N-formimidoyl thienamycin (MK0787), was tested against 46 laboratory reference strains and 2,158 clinical isolates of gram-positive and -negative bacteria, including anaerobes, and compared with cefoxitin, cefaxolin, carbenicillin, and amikacin. MK0787 was significantly more active than the reference antibiotics against most bacteria tests. MK0787 was 16- to 500-fold more active than the other antibiotics against Staphylococcus aureus, Streptococcus pneumoniae, and group A and group B streptococci, inhibiting most isolates at concentrations less than 0.031 micrograms/ml. The inhibition concentration against over 90% of 156 strains of Streptococcus faecalis was 1 micrograms/ml. MK0787 had slightly less activity than carbenicillin against Haemophilus influenzae. The minimal inhibitory concentrations of MK0787 against strains of Enterobacter spp., Citrobacter spp., Serratia marcescems. Pseudomonas aeruginosa, and Clostridium difficile that are resistant to currently available antibiotics were less than or equal to 4 micrograms/ml. The only species found resistant to MK0787 was Pseudomonas maltophilia, which was equally nonsusceptible to the other reference antibiotics.